2007
DOI: 10.1177/0091270007300953
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, Pharmacokinetics, and Neuroendocrine Effects of PRX‐00023, a Novel 5‐HT1A Agonist, in Healthy Subjects

Abstract: PRX-00023 is a novel, nonazapirone 5-HT1A agonist in clinical development for treatment of affective disorders. The objectives of the initial clinical phase I studies (a single ascending dose study and multiple dose-ascending and high-dose titration studies) were to measure the pharmacokinetics, pharmacodynamic (neuroendocrine) effects, and tolerability of PRX-00023 in healthy subjects. The studies evaluated 10-mg to 150-mg doses of PRX-00023 in up to 112 healthy male and female subjects aged 18 to 54 years. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this study, AL‐8309 was safe and well tolerated in these healthy adult male subjects. There were no serious adverse events related to the radioactive dose, and all treatment‐associated events (lightheadedness and dizziness) were mild in intensity and related more to the 5HT1A agonism effects 11 . This is the first reported use of AMS technology with a topically applied ophthalmic product.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this study, AL‐8309 was safe and well tolerated in these healthy adult male subjects. There were no serious adverse events related to the radioactive dose, and all treatment‐associated events (lightheadedness and dizziness) were mild in intensity and related more to the 5HT1A agonism effects 11 . This is the first reported use of AMS technology with a topically applied ophthalmic product.…”
Section: Discussionmentioning
confidence: 82%
“…There were no serious adverse events related to the radioactive dose, and all treatment-associated events (lightheadedness and dizziness) were mild in intensity and related more to the 5HT1A agonism effects. 11 This is the first reported use of AMS technology with a topically applied ophthalmic product. The results from the present study guided the team to continue monitoring metabolites observed to be greater than 10% of the parent drug exposure in the future AL-8309 clinical trials.…”
Section: Discussionmentioning
confidence: 95%